One Health Approach: Researchable Areas for Stakeholders - Phand, Shamali; Kumari, Veenita; Phand, Shahaji (Journal of Agricultural Extension Management, 2022)
One Health is a collaborative, multisectoral, and transdisciplinary approach working at the local, regional, national, and global levels with the goal of achieving optimal health outcomes recognizing the interconnection between people, animals, plants, and their shared environment. One health is approach which recognizes that health of people is closely associated with animal health and our shared environment. In 2004, Wildlife Conservation Society gave the concept of “One world, One health”. One health approach is very important factor to safeguard human health and increase the pandemic preparedness like covid19. Increased animal human interface indicates the need of one health approach. Execution of one health approach will help to achieve the UN agenda 2030 that is sustainability development goals. This study is based on desk research and review of secondry data and published literature on the topic. To support the secondary data, the primary data was collected via structured google form questionnaire to the five concerned stakeholders with total sample size 25 and panel discussion with five renowned experts. Study found many researchable areas w.r.t concerned stakeholders. Recommendation in areas of one health is explained in this study. There is need of extension institute like MANAGE to step into one health concept in context of capacity building and providing common platform for all concerned stakeholders